Media massa Studi Kepercayaan Publik Terhadap Pemberitaan Media Konvensional Dan New Media Di Kelurahan Prabumulih - Muhammad Aqsal Aqsal; Sumaina Duku; Jufrizal (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2023)
Â This thesis is entitled "Public Trust in Conventional Media and New Media Reporting (Study in RW 02 village Prabumulih" with the problems in this research are: the level of public trust in Conventional Media and New Media and what are the factors that influence public trust and distrust towards Conventional Media and New Media. The method used in this study is a quantitative method to get more and more accurate data. The data collection technique is a questionnaire or questionnaire, the data analysis technique is to use a percentage formula which is managed with simplified numbers in tabulation form as well as the results of the interviews which will be written based on the data obtained. The results of this study indicate that people trust and like New Media more than Conventional Media, while the causes and factors of people's trust and disbelief in the two media are the advantages and disadvantages that both media have.